2002
DOI: 10.1023/a:1019896822588
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Increased alcohol consumption is associated with substantial morbidity and mortality in young and middle-aged adult populations, but its effects on the health of older adults have received less attention. The objective of the study was to review published studies that assessed the effects of alcohol on falls or fall injuries, functional impairment, cognitive impairment, and all-cause mortality among older adults. MEDLINE database and bibliographies of selected citations were searched for English language studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…The J-shaped association between alcohol intake and mortality has been established almost exclusively in studies of younger and middle-aged adult populations. In older people, however, this association has not been confirmed [13]. …”
Section: Alcohol Consumptionmentioning
confidence: 99%
See 2 more Smart Citations
“…The J-shaped association between alcohol intake and mortality has been established almost exclusively in studies of younger and middle-aged adult populations. In older people, however, this association has not been confirmed [13]. …”
Section: Alcohol Consumptionmentioning
confidence: 99%
“…In contrast, 4 studies that used a comparable definition of alcohol consumption reported an inverse association between mortality and increased alcohol intake. Furthermore, another 13 studies found no association between alcohol intake and mortality among people ≥60 years [13]. …”
Section: Alcohol Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The preservation of independent functional ability is an important goal for many older adults, and there is a growing interest in the connection between alcohol consumption and physical and mental functioning among the older adult population. Although results from earlier studies on the association between alcohol use and functional disabilities were mixed (Reid et al, 2002), findings from more recent publications have been more consistent in suggesting the association between low to moderate alcohol use and lower risk of functional impairments among older adults (Cawthon et al, 2007; Chen & Hardy, 2009; Karlamangla et al, 2009; Lang et al, 2007; Lee et al, 2009; Maraldi et al, 2009; Sun et al, 2009; Wang et al, 2002). …”
Section: Introductionmentioning
confidence: 95%
“…Overconsumption of alcohol may increase the likelihood of cognitive impairment, self-neglect, falls and other health risks in older people [1]. Mild-to-moderate alcohol consumption, on the other hand, has been shown to associate with health benefits including better cardiac and cerebrovascular health [2], decreased risk for dementia [3] as well as increased psychological wellbeing and improved quality of life [4].…”
Section: Introductionmentioning
confidence: 99%